ДИАГНОСТИКА И ЛЕЧЕНИЕ УРОГЕНИТАЛЬНЫХ ИНФЕКЦИЙ В ОБЩЕЙ ПРАКТИКЕ - С. С. Вялов (SINAPS LLC, 2012)
The article presents current data on the laboratory diagnosis of urogenital infections. Recommendations on the tactics of the management of patients with clinical and laboratory signs of the urogenital infections are given. The possibility of using various antimicrobials include antiviral was investigated. The choice of drugs for treatment was discussed.